Israel and the world economy the power of globalization - Razin, Assaf (The MIT Press, 2018)
"This book provides rigorous analysis of some of the major episodes during Israel's economic transition and spells out, empirically, how globalization played a crucial role in advancing Israel's economic progress. Economists and policy makers can gain insights as to how a globalized economy can take advantage of international trade, labor mobility, its international financial links, while at the same time navigate shocks like the 2008 global financial crisis. It discusses the collapse of the Soviet Union and the massive wave of high skill immigration to Israel which followed; the Great Moderation in inflation and employment fluctuations in the advanced economies, and the convergence of Israel's inflation to the low world inflation rates; the 2008 Global Financial Crisis and the surprising robust performance of the Israeli economy; the rise of the Asian markets, recently opened up to Israel's exports, which became abundant source of outward foreign direct investments; the global information technology surge and its spillovers to the emerging high-tech sector in Israel; brain drain facilitated by Israel's higher education system; and the economic implications of the Palestinian-Israeli crisis. In addition to analyzing the past and current state of Israel, the book compares developments within the Israeli economy to developed and emerging-market economies in similar circumstances. It combines economic theory with empirical evidence, and includes a review of the literature covering earlier stages of Israel's economic development."--Provided by publisher.